Workplace Wellness Programs Study : Final Report - Soeren Mattke, Hangsheng Liu (RAND Corporation, 2013)
Over the last several decades, an epidemic of â€œlifestyle diseasesâ€ has developed in the United States: Unhealthy lifestyles, such as inactivity, poor nutrition, tobacco use, and frequent alcohol consumption, are driving up the prevalence of chronic disease, such as diabetes, heart disease, and chronic pulmonary conditions. These chronic conditions have become a major burden, as they lead to decreased quality of life, premature death and disability, and increased health care cost. Furthermore, although chronic disease was once thought to be a problem of older age groups, there is a shift toward onset during Americansâ€™ working age that adds to the economic burden, because of illness-Ââ€related loss of productivity due to absence from work (absenteeism) and reduced performance while at work (presenteeism).